DISORDERS OF INNATE IMMUNITY IN VARIOUS FORMS OF THE CHRONIC ECZEMA - Lysenko, K.I.; Bolotna, L.A.; Sarian, O.I.; Dudchenko, M.O. (World of Medicine and Biology, 2022)
The role of adaptive immunity in the mechanism of development of eczema as a chronic relapsing dermatosis is proven. The infectious nature of the process in microbial eczema, dysbiosis of skin microbiota and frequent bacterial complications in idiopathic (genuine) eczema primarily indicate disorders of innate immunity. The purpose of the study was to determine the cellular and humoral links of innate immunity in patients with various clinical forms of chronic eczema. Suppression of phagocytic activity of neutrophils in patients with microbial eczema due to weakening the absorbing and digesting ability (decrease in the value of the phagocytic index, phagocytic number and index of completion of phagocytosis) was established, while in patients with idiopathic eczema only the index of completion of phagocytosis was reliably reduced. For the first time, a decreased level of the antimicrobial protein lactoferrin was determined in both forms of dermatosis compared to that in individuals of the control group. The level of the antimicrobial peptide β-defensin 2 increased in all patients relative to that in the control group, more significantly in idiopathic eczema.